Cost Sharing Paid by Social Askes Participants at Pelamonia Hospital Makassar and Faisal Islamic Hospital Makassar - Nurseskasatmata, Satria Eureka; Rasyid, Djusmadi; Sakriawati, Sakriawati; Pannyiwi, Rahmat; Saputra, M. Khalid Fredy (International Journal of Health Sciences, 2024)
The cost of hospital services in Indonesia in general is a complex problem with many obstacles and we can see that the publication of cost information is often unclear. In Government Hospitals, in particular, budget allocations are still inadequate, this is due, among other things, to the costs that must be borne by the Hospital, especially equipment costs, operational and maintenance costs, which seem to tend to increase following advances in increasingly sophisticated health technology. The aim of the research is to obtain an overview of the cost sharing that will be incurred by Askes Social participants at Pelamonia Hospital and Islamic Faisal Hospital Makassar, reviewed in terms of additional costs incurred/types of patient inpatient treatment in terms of class/rank and linked to Regional Regulations. The type of research used is survey research with a descriptive approach, with the aim of obtaining information about cost sharing costs for health services in the inpatient unit of Pelamonia Hospital Makassar and Islamic Faisal Hospital Makassar. The results of this study and previous research show that patients participating in Askes tend to use nursing classes that are better than those specified. The conclusion is that the Cost Sharing for Social Health Insurance patients based on group/rank in the inpatient unit at Faisal Islamic Hospital is IDR 795,000,- while at Pelamonia Hospital Makassar it is IDR 1,125,000.